Differences in The Incidence of Urinary Tract Infection (UTI) in Women Using Herbal and Non-Herbal Sanitary Napkins - Yanti, Rahma; Silviani, Yusianti (Jurnal Biologi Tropis, 2025)
Urinary Tract Infection (UTI) is a common health issue among women, including those caused by the use of menstrual pads. This study aims to investigate the difference in the incidence of UTI between women using herbal and non-herbal pads at Prodia Clinical Laboratory in Palembang. This research employed an analytical observational design with 31 female employees as subjects. Sampling was conducted using a questionnaire and complete urine tests, including dipstick and microscopic examination. The results showed that 10.5% of non-herbal pad users were suspected of having UTI, while no herbal pad users were suspected of having UTI. Based on the Mann Whitney U statistical test, no significant differences were found between the two groups (p > 0.05). This study concluded that there is no significant difference in the incidence of UTI between users of herbal and non-herbal pads. Further research with a larger sample size is recommended to confirm these findings.